Outside board director experience and the growth of new ventures - Harutyunyan, Tatevik; Timmermans, Bram; Frederiksen, Lars (Journal of Business Venturing, 2025)
Most research on entrepreneurship focuses on entrepreneurs' human and social capital as the drivers of new venture performance. However, less is known about how much the endowments of other strategic human resources, namely board directors, influence new venture performance. To generate new insights on this topic, we theorize and empirically investigate to what extent, and under which conditions, the experience of outside board directors affects new venture growth. Our analysis of Norwegian registry data on 15,594 new ventures does not provide immediate evidence that the presence of outside board directors or their experiences drive new venture growth. However, post hoc analysis suggests that the timing of board entry, combined with industry and directorial experience, plays a significant role in shaping growth outcomes. Additionally, the impact of industrial and directorial experience varies depending on the industry environment. • Outside board directors bring limited benefit to new ventures unless they have specialized expertise and proven experience. • The impact of outside board experience is greatest for newly appointed members with with industry experience. • Appointment timing matters: combining industry expertise with directorial background in outside board members drives growth. • In volatile sectors, outside directors with industry expertise provide much more benefit than directorial background alone.